Dead-time effects on the voltage spectrum of a PWM inverter - Moore, David C.; Odavic, Milijana; Cox, Stephen M. (Oxford University Press, 2014)
An inverter converts a direct-current power supply to an alternating-current power supply. This con- version is achieved by switching the output between the inputs at high frequency. The resulting output voltage may be described by a high-frequency train of variable-width pulses. Pulse widths are slowly modulated so that this output waveform contains a prescribed low-frequency component, which may then be isolated by an appropriate filtering regime. Techniques for determining the full harmonic spec- trum of input and output voltages and currents are well established, at least for an idealised mathematical model of the inverter. However, this model assumes that changes of inverter configuration can be ef- fected instantaneously, which is not quite the case in practice. In fact, a small amount of dead time must be incorporated into switching regimes in order to avoid short circuits of the input. Although dead time is an important feature of real power conversion devices, its effects on output voltage spectra have not previously been fully determined (except by imposing rather restrictive approximations). This situation is remedied in the present paper, in which we present closed-form expressions for the coefficients of the harmonic spectrum, corroborated by simulations.